2014
DOI: 10.1371/journal.pone.0099182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Association Mapping Approaches for Blast Resistant Genes in Finger Millet Using SSRs

Abstract: The major limiting factor for production and productivity of finger millet crop is blast disease caused by Magnaporthe grisea. Since, the genome sequence information available in finger millet crop is scarce, comparative genomics plays a very important role in identification of genes/QTLs linked to the blast resistance genes using SSR markers. In the present study, a total of 58 genic SSRs were developed for use in genetic analysis of a global collection of 190 finger millet genotypes. The 58 SSRs yielded nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 35 publications
(43 reference statements)
4
66
2
Order By: Relevance
“…Only 20 primers showed polymorphism, and 13 primers were identified as having a PIC value above 0.5. Later, Kalyana Babu et al (2014b) used two search criteria for identification of EST-SSRs. In the first criterion, the minimum number of repeats was 6 for dinucleotide, 4 for trinucleotide, and three for tetra, penta and hexa-nucleotides.…”
Section: Molecular Markers For Assessing Genetic Diversity Species Rmentioning
confidence: 99%
See 3 more Smart Citations
“…Only 20 primers showed polymorphism, and 13 primers were identified as having a PIC value above 0.5. Later, Kalyana Babu et al (2014b) used two search criteria for identification of EST-SSRs. In the first criterion, the minimum number of repeats was 6 for dinucleotide, 4 for trinucleotide, and three for tetra, penta and hexa-nucleotides.…”
Section: Molecular Markers For Assessing Genetic Diversity Species Rmentioning
confidence: 99%
“…Kalyana Babu et al (2014a) identified four markers UGEP 81, UGEP 77, UGEP 90, and FM 9 tightly linked to QTLs of basal tiller number, days to flowering, flag leaf blade width and plant height, respectively. For blast resistance, 104 SSR markers identified four QTLs for finger blast and one QTL for neck blast resistance (Kalyana Babu et al, 2014b). The rice genomic marker RM 262 and genic marker FMBLEST32 were linked to finger blast disease resistance at a P -value of 0.007 and explained a low phenotypic variance of 10 and 8% respectively (Table 2).…”
Section: Association Mapping Of Important Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…To develop molecular markers for MAS and breeding in finger millet for fungal blast disease resistance, Panwar et al (2011) have reported developing EST-based resistance gene analogue (RGA) markers. A comparative genomics approach was used to establish association of SSR markers to finger millet blast disease resistant QTL (Babu et al, 2014). Isolation of candidate genes and gene families, such as RGAs Weng et al, 2009), SiNAC (Puranik et al, 2011a), Dof1 (Gupta et al, 2012), and calcium sensor CaM gene (Nath et al, 2010), from finger millet and foxtail millet in the past few years has provided opportunities to develop functional markers for MAS and breeding for nutritional quality improvement and blast disease resistance.…”
Section: A Molecular Marker Resources and Genetic Mapsmentioning
confidence: 99%